Etika Guru dalam Pemikiran Habib Sayyid Idrus Bin Salim Aljufri Studi Literatur Dalam Penerapan di pendidikan Alkhairaat - Gaus, Djulaiha (Jurnal Pendidikan dan Ekonomi (JUPEK), 2024)
The research method used in this research is a literature review, where the author completes all the readings related to the history of Sayyid Idrus' journey in establishing the madrasah to how Sayyid Idrus' ethics implemented the learning curriculum in the Alkhairaat madrasah. The results of the research show that to be an ideal educator you must first have a sense of "mahabbah", a feeling of love that if expressed in a profession, be it a teacher or whatever, then naturally he will be willing to do anything as long as the target object feels happy and content